ANALISIS FAKTOR YANG MEMPENGARUHI PERSEPSI MAHASISWA TERHADAP PELUANG BISNIS DAN MINAT MENJADI ENTREPRENEUR - Kukuh Mulyanto (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2018)
his paper aims to identify the factorthat influence the perception ofbusiness opportunities, and the latter’s influence onentrepreneurial intention.The research method was sensus with quantitative analysis approach. Themodel is tested on Totalwin College of Business students.Data was collectedwith questionnaires. By applying a structural equationmodel, we observedthat the perception of self abilities (self-efficacy) positively andsignificantlyaffects both the perception of opportunities and entrepreneurial intention,andthat the perception of opportunities affects entrepreneurial intention.